The CARMENES search for exoplanets around M dwarfs: The He I infrared triplet lines in PHOENIX models of M 2-3 V stars - Hintz, Dominik; Fuhrmeister, B.; Czesla, S.; Schmitt, J. H. M. M.; Schweitzer, A.; Nagel, E.; Johnson, E. N.; Caballero, J. A.; Zechmeister, M.; Jeffers, S. V.; Reiners, A.; Ribas, I.; et al. (Astronomy and astrophysics, 2020)
The HeI infrared (IR) line at a vacuum wavelength of 10 833 angstrom is a diagnostic for the investigation of atmospheres of stars and planets orbiting them. For the first time, we study the behavior of the HeI IR line in a set of chromospheric models for M-dwarf stars, whose much denser chromospheres may favor collisions for the level population over photoionization and recombination, which are believed to be dominant in solar-type stars. For this purpose, we use published PHOENIX models for stars of spectral types M2 V and M3 V and also compute new series of models with different levels of activity following an ansatz developed for the case of the Sun. We perform a detailed analysis of the behavior of the HeI IR line within these models. We evaluate the line in relation to other chromospheric lines and also the influence of the extreme ultraviolet (EUV) radiation field. The analysis of the HeI IR line strengths as a function of the respective EUV radiation field strengths suggests that the mechanism of photoionization and recombination is necessary to form the line for inactive models, while collisions start to play a role in our most active models. Moreover, the published model set, which is optimized in the ranges of the NaI D-2, H alpha, and the bluest CaII IR triplet line, gives an adequate prediction of the HeI IR line for most stars of the stellar sample. Because especially the most inactive stars with weak HeI IR lines are fit worst by our models, it seems that our assumption of a 100% filling factor of a single inactive component no longer holds for these stars.
Gesehen am 08.10.2020